Engineering Parvalbumin for the Heart: Optimizing the Mg2+ Binding Properties of Rat β-Parvalbumin - Zhang, Jianchao; Shettigar, Vikram; Kindell, Daniel G.; Liu, Xiaotong; Lopez, Joseph J.; Yerrimuni, Vinatham; Davis, Grace A.; Davis, Jonathan P. (Frontiers in Physiology, 2011)
Parvalbumin (PV), an EF-hand protein family member, is a delayed calcium buffer that exchanges magnesium for calcium to facilitate fast skeletal muscle relaxation. Genetic approaches that express parvalbumin in the heart also enhance relaxation and show promise of being therapeutic against various cardiac diseases where relaxation is compromised. Unfortunately, skeletal muscle PVs have very slow rates of Ca2+ dissociation and are prone to becoming saturated with Ca2+, eventually losing their buffering capability within the constantly beating heart. In order for PV to have a more therapeutic potential in the heart, a PV with faster rates of calcium dissociation and high Mg2+ affinity is needed. We demonstrate that at 35oC, rat β-PV has an 30-fold faster rate of Ca2+ dissociation compared to rat skeletal muscle α-PV, and still possesses a physiologically relevant Ca2+ affinity ( 100 nM). However, rat β-PV will not be a delayed Ca2+ buffer since its Mg2+ affinity is too low ( 1 mM). We have engineered two mutations into rat β-PV, S55D and E62D, when observed alone increase Mg2+ affinity up to 5-fold, but when combined increase Mg2+ affinity 13-fold, well within a physiologically relevant affinity. Furthermore, the Mg2+ dissociation rate (172/s) from the engineered S55D, E62D PV is slow enough for delayed Ca2+ buffering. Additionally, the engineered PV retains a high Ca2+ affinity (132 nM) and fast rate of Ca2+ dissociation (64/s). These PV design strategies hold promise for the development of new therapies to remediate relaxation abnormalities in different heart diseases and heart failure.